In Vivo Regenerative Potential of Coprinus comatus in Pancreatic Tissue After Acute Stress with Chronic Consequences - Nebojša Stilinović; Ana Tomas; Saša Vukmirović; Nebojša Kladar; Miloš Čanković; Maja Đanić; Michał Seweryn Karbownik; Aleksandar Rašković; Ivan Čapo (Molecules)
The edible mushroom Coprinus comatus has a long history of use in metabolic diseases, which is increasingly documented by modern research. Due to its favorable nutritional composition, it was assumed that this mushroom could accelerate tissue recovery after acutely induced damage with subsequent disturbance of primarily carbohydrate metabolism. To test this hypothesis, the alloxan diabetes model was used, where experimental animals’ change in body weight and biochemical and histological indicators of recovery were monitored. Before performing the in vivo part, HPLC analysis of the C. comatus extract was carried out with subsequent in silico and in vitro tests. Comparing the animals treated with the mushroom in three different doses, no significant change in body weight was observed. Still, the change was also noticed in the lipid status and glycemia, with a dose-dependent beneficial effect. Morphometric analysis of pancreatic tissue stained by immuno-histochemical methods showed that long-term treatment with C. comatus leads to increased numerical density, nuclear volume, and absolute number of beta cells of the islets of Langerhans, which suffered severe damage after alloxan administration. Overall, C. comatus may contribute to faster tissue recovery after acute diabetic-relevant damage with chronic consequences.